If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15(1t + 6m) + 9t = 6 Reorder the terms: 15(6m + 1t) + 9t = 6 (6m * 15 + 1t * 15) + 9t = 6 (90m + 15t) + 9t = 6 Combine like terms: 15t + 9t = 24t 90m + 24t = 6 Solving 90m + 24t = 6 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-24t' to each side of the equation. 90m + 24t + -24t = 6 + -24t Combine like terms: 24t + -24t = 0 90m + 0 = 6 + -24t 90m = 6 + -24t Divide each side by '90'. m = 0.06666666667 + -0.2666666667t Simplifying m = 0.06666666667 + -0.2666666667t
| 7x-24+5x+18=180 | | x^2-3x=29 | | (3f)+2=11 | | -8st+5t+2u-1=8t+9u-9 | | 170=45t | | 10b-9-3b=2 | | 170-t=45 | | 45=170t | | 4x-6-5x-5=x-4 | | 100=x^2+10x+25 | | (9x+59)+(6x-6)+(3x+8)+(12x+29)=360 | | /8+/50+2/2= | | 162=-8x+10 | | -7(p+1)+3=-18-5p | | -4u+4u-9= | | 28x-7=26 | | -6x^2+54x-48=0 | | 8+x=x-1 | | -3u-8u= | | t-81+50=-7 | | 3(3x-6)+4(-5x-1)=-8 | | 13+x=47 | | 4x-6-5x+5=x-4 | | -10n+12=-6n-16 | | -4(2x+3)=-8x-12 | | 8u^2+10u^2= | | 8(3x-6)+4(-5x-1)=-8- | | 36a^4+108a^3+77a-12a-9= | | 2x+8-20=-3x-(-18) | | x+(x+1)+(x+2)+(x+3)=26 | | (4x+8)+(9x-43)+(8x+9)+(5x+48)=360 | | -19+11x=9+10x |